The effects of electricity prices and electricity supply on the economic growth of South Africa for the period 1993 to 2022 - Mokgobi, Dubi Paulette (My University, 2025)
As an energy source, electricity is fundamental in driving economic growth, particularly in emerging economies like South Africa. This study investigated the effects of electricity prices and supply on South Africa's economic growth over the 1993 to 2022 period. This is performed by adopting and extending the energy-growth model, this study contributes to the existing literature on energy economics. To achieve the research objective, unit root tests were conducted to identify the integration order of variables, followed by the Autoregressive Distributed Lag (ARDL) approach to estimate short- and long-run relationships. The bounds test confirmed a long-run equilibrium relationship between the variables in the energy-growth model. The ARDL results revealed that electricity prices positively influence economic growth in the short and long run. The electricity supply negatively impacts economic growth in the short run but is statistically insignificant in the long run. Additionally, the results indicate a negative and statistically significant long-run relationship between labour force participation and economic growth, highlighting potential structural inefficiencies in South Africa's labour market. These findings empirically validate aspects of the energy consumption theory while emphasising developing country-specific dynamics. The study recommends proactive government policies to address high electricity prices and irregular supply, which pose significant risks to economic development
Thesis (M. Com. (Economics)) -- University of Limpopo, 2025
Keywords: Electricity prices; Economic growth; Energy consumption theory; RDL model; South Africa; Electric power consumption; Economic development -- South Africa; Energy consumption; Sustainable development -- South Africa